Full size shape of the forward mould hung on Patrick Lainey's shed wall - Parsons, Lawrence (1987)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Fieldwork and Personal Impressions of Black Duck Brook and Winterhouse ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Fieldwork and Personal Impressions of Black Duck Brook and Winterhouse."